TEACHING LIBRARY: KONSEP, MISI, STANDAR, DAN SASARAN - Rusmono, Doddy (Universitas Pendidikan Indonesia, 2012)
Planning of Teaching Library (TLib.) as an entity involves steps of examining environments, conducting needs assessments, and evaluating available resources. In its implementation, TLib. affirms librarian to holds a position as more than just a supporting element for academic programs and research. The role librarian plays as a major organizer of intellectual asset brings with it some responsibility of teaching users to get well informed and benefit sources of information available and at the same time encouraging the opportunity of lifelong learning through continuous teaching-learning process. To librarian, teaching proves to be a supporting activity towards credits to enhance his career as professional. In regards with the concept of TLib. teaching is geared towards illuminating efficient techniques to evaluate and provide information for various kinds of users in the society. Giving new students especially, bibliographic instructions of how to benefit from the collections the best way through User Education effectively. Delivering materials of librarianship to information communities from both outside and inside the campus: in-house training, practices for vocational school students majoring in Information and Communication Technology (ICT), comparative study, and benchmarking. As information specialist and subject librarian as well, this professional guides a new paradigm with vision and mission basically doing some strengthening on the motto the university has, namely â€œA leading and outstanding universityâ€. Standards serving as an objective tool are applied based on performance measurements and referred to the correlation between information resources served and the achievement of the Civitas Academica (CA) of the university in a more intense way. The TLib.â€™s goals as the implementation of standards are focused on users as stakeholders and range from the empowerment to the preservation of knowledge and culture.